2020
DOI: 10.7717/peerj.9790
|View full text |Cite
|
Sign up to set email alerts
|

The role of textiles as fomites in the healthcare environment: a review of the infection control risk

Abstract: Background Infectious diseases are a significant threat in both healthcare and community settings. Healthcare associated infections (HCAIs) in particular are a leading cause of complications during hospitalisation. Contamination of the healthcare environment is recognised as a source of infectious disease yet the significance of porous surfaces including healthcare textiles as fomites is not well understood. It is currently assumed there is little infection risk from textiles due to a lack of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 100 publications
0
43
0
2
Order By: Relevance
“…Hospital patients and personnel are at risk of nosocomial viral infections [ 8 , 27 ], as clearly manifested during the current COVID-19 pandemic [ 28 , 29 ]. Textiles, especially reusable healthcare textiles that are in close contact with patients for extended periods of time, can significantly contribute to bacterial, fungal and viral nosocomial infections [ 30 , 31 , 32 ]. It has been found that indirect cross-contamination through transmission of microorganisms, including viruses, which remain infectious on fomite soft and hard surfaces, can contribute to nosocomial infections [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hospital patients and personnel are at risk of nosocomial viral infections [ 8 , 27 ], as clearly manifested during the current COVID-19 pandemic [ 28 , 29 ]. Textiles, especially reusable healthcare textiles that are in close contact with patients for extended periods of time, can significantly contribute to bacterial, fungal and viral nosocomial infections [ 30 , 31 , 32 ]. It has been found that indirect cross-contamination through transmission of microorganisms, including viruses, which remain infectious on fomite soft and hard surfaces, can contribute to nosocomial infections [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…There does not appear to be any research on the stability of SARS-CoV-2 or other coronaviruses on textiles during laundering. The persistence of SARS-CoV-2 on laundered textiles could lead to cross-contamination of other textiles within the wash and pose a risk of transmission to the end user; this is of particular concern within the health care sector, where patients are clinically vulnerable ( 12 ). In this study, the stability of HCoV-OC43 on cotton during laundering was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the transfer efficiency of bacteria was greater from woven viscose and polyester than from cotton, silk, and polypropylene ( 11 ). Increasing our understanding of the potential risk of SARS-CoV-2 persistence on textiles is of particular importance in health care settings to inform infection control policies for handling used linen and staff uniforms before laundering in the domestic, care home, and hospital environments ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laundering processes reduce the microbial load on textiles with an aim to remove soiling and potential pathogens to minimise the risk of infection, rather than completely sterilise the textiles (Bockmühl 2017; Owen and Laird 2020). Healthcare linens including bed sheets and hospital gowns are laundered industrially, employing thermal disinfection (60–71°C) or chemo‐thermal disinfection (Department of Health 2016).…”
Section: Introductionmentioning
confidence: 99%